Evaluation of prevalence's of pfdhfr and pfdhps mutations in Angola - Ferreira, Dinora (2021)
Background: Malaria is the major cause of morbidity and mortality in Angola. The most vulnerable groups to Plasmodium falciparum infection are pregnant women and children under five years of age. The use of an intermittent preventive treatment (IPT) with sulphadoxine/pyrimethamine (SP) in pregnant women was introduced in Angola in 2006 by the National Malaria Control Programme, and currently this strategy has been considered to be used for children malaria control. Considering the previous wide use of SP combination in Angola, together to the reported cases of SP treatment failure it is crucial the evaluation of the prevalence of five mutations in pfdhfr and pfdhps genes associated to P. falciparum resistance to SP before the introduction of S/P IPT in children. Methods: The study was conducted in five provinces, with different transmission intensities: Huambo, Cabinda, Uíge, Kwanza Norte, and Malanje. The detection of the mutations in pfdhfr and pfdhps genes was carried out in 452 P. falciparum blood samples by PCR RFLP. Results: For pfdhfr gene, 90,3% of the samples carried the mutation 51I, with 7.5% of mixed infections; 51% carried wild type allele 59C, with 29.2% mixed infections and; 99.1% of isolates harboured the mutant allele 108N. Concerning, pfdhps gene, 83,1% were mutant type 437G with 11% mixed infections , while 87% of the studied isolates were wild type for codon 540. Discussion: This is the first representative epidemiological study of the whole Angola country on the prevalence of the genotypes associated with SP chemoresistance. A high frequency of individual mutations in both genes (51I and 108N in pfdhfr, and 437G in pfdhps) was found, besides a low prevalence of the quintuple mutation. Conclusion: The data showed that the implementation IPT using SP in children needs to be reviewed.